2019
DOI: 10.1093/ej/uez041
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Schools and Strategic Pupil Exclusion

Abstract: This paper studies whether pupil performance gains achieved by autonomous schools -specifically academy schools in England -can be attributed to the strategic exclusion of poorly performing pupils. In England there have been two phases of academy school introduction, the first in the 2000s being a school improvement programme for schools serving disadvantaged pupil populations, the second a mass academisation programme in the 2010s which by contrast enabled better performing schools to become academies. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This possibility is supported by anecdotal data in non‐ministerial government reports; hence, the Office of the School’s Adjudicator (OSA, 2017) reports third‐party accounts of ‘coerced home education’ across year groups which suggest that exertion of pressure on parents by schools to remove their children is widespread or more common than supposed. In Machin and Sandi (2020), higher rates of legal exclusion were found to be associated with the pre‐2010 academisation of poorly performing urban schools, such that any gains in academic performance were linked to the addressing of disciplinary issues. The later mass academisation did not, Machin and Sandi (2020) found, lead to increased formal exclusion rates because the schools in question were predominantly already higher‐performing schools without significant behaviour or discipline issues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This possibility is supported by anecdotal data in non‐ministerial government reports; hence, the Office of the School’s Adjudicator (OSA, 2017) reports third‐party accounts of ‘coerced home education’ across year groups which suggest that exertion of pressure on parents by schools to remove their children is widespread or more common than supposed. In Machin and Sandi (2020), higher rates of legal exclusion were found to be associated with the pre‐2010 academisation of poorly performing urban schools, such that any gains in academic performance were linked to the addressing of disciplinary issues. The later mass academisation did not, Machin and Sandi (2020) found, lead to increased formal exclusion rates because the schools in question were predominantly already higher‐performing schools without significant behaviour or discipline issues.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Children and Families Act of 2014 (DfE, 2014), the parents of children classified as having ‘special’ educational needs and/or disabilities (SEND) are legally entitled to select a mainstream school for their child, yet, such children are disproportionately represented in official exclusion data and ‘off‐rolling’ data, as are disadvantaged pupils (Graham et al., 2019, p. 5). Power and Taylor (2020) outline varied legal practices that can be considered exclusionary, despite being portrayed or discursively constituted as ameliorative, including isolation from peers in ‘nurture groups’ or ‘pupil referral units’, whereas this article focuses primarily on ‘off‐rolling’ as ‘strategic pupil exclusion’ (Machin & Sandi, 2020, p. 125); that is, ‘off‐rolling’ as strategic manipulation of academic performance data. England’s national school inspectorate (Ofsted, 2018, 2019a–c) condemns ‘off‐rolling’ and discursively constitutes head teachers suspected of engaging in such practices as a misguided minority (Done & Knowler, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such situations, students who do not submit to the rules (Lloyd, 2008) become 'collateral casualties' (Bauman, 2004), who find themselves locked in a process in which they are evacuated to the social margins of schooling (Slee, 2012). However, a recent study by Machin and Sandi (2018) suggested that there is a need for a nuanced account of the relationship between competition and exclusion, as exclusion is not always a means of facilitating better performance for autonomous schools in published league tables. They suggested that increases in school exclusions may partly be a consequence of disciplinary behaviour procedures that some schools elect to implement as well as increasing pressure by parents and other bodies to ensure the school environment is protected from potential disruption.…”
Section: School Exclusion and Send In Englandmentioning
confidence: 99%